Energy transfers between aerodynamic and acoustic fields in a rectangular impinging jet - Hassan H. Assoum; Jana Hamdi; Mouhammad El Hassan; Tarek Mrach; Kamel Abed Meraim; Anas Sakout (Energy Reports, 2020)
Ventilation systems in buildings are of vital importance for the provision of acceptable thermal conditions and air quality while meeting stringent energy requirements. When a rectangular jet hits a slotted plate, an acoustic disturbance can be generated and self-sustained tones produced. Self-sustaining tones appear when a feedback loop develops between the surface of impact and the jet instabilities near to the jet exit. In order to control this phenomenon, more attention should be given to the source of energy that amplifies the resulting noise. Few studies have considered the fluctuation of the aerodynamic field using High Speed 3D Tomographic-PIV in the presence of self-sustaining tones. In this work, we investigate energy transfer between the aerodynamic and acoustic fields for different Reynolds numbers (Re = 5294 and Re = 5956) to better understand the noise generated by a rectangular jet impinging on a slotted plate. High Speed 3D Tomographic-PIV was performed at a sampling rate of 2 KHz and main flow vortices frequencies below 0.4 KHz. It was found that in the case of an optimal configuration for self-sustaining tones, the fluctuation of the Z-component of velocity presented higher amplitudes near the jet exit region.
Keywords: 330; Impinging jet; Tomographic-PIV; Turbulent kinetic energy; Self-sustaining tones